2011
DOI: 10.1111/j.1600-6143.2011.03636.x
|View full text |Cite
|
Sign up to set email alerts
|

Virologic and Immunologic Monitoring of Cytomegalovirus to Guide Preemptive Therapy in Solid-Organ Transplantation

Abstract: Control of human cytomegalovirus (HCMV) infection during the posttransplant period was investigated in134 solid-organ transplant recipients by monitoring in parallel virologic and immunologic parameters for at least 1 year of follow-up. Virologic monitoring was achieved by determining HCMV DNAemia with real-time PCR, using the threshold of 300 000 DNA copies/mL blood as a cutoff for starting preemptive therapy. Immunologic monitoring included measurement of HCMV-specific CD4+ and CD8+ T cells by cytokine flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 37 publications
7
77
1
3
Order By: Relevance
“…DNAemia was quantified weekly or bi-weekly upon occurrence of active HCMV infection. Pre-emptive antiviral therapy was given to Tx patients reaching a DNAemia cut-off of 300 000 DNA copies ml À1 whole blood (Lilleri et al, 2004;Gerna et al, 2007Gerna et al, , 2011 and consisted of iv ganciclovir (GCV) at a dosage of 5 mg kg À1 twice a day, or oral valganciclovir (VGCV), 900 mg twice a day. Antiviral therapy was continued until the virus disappeared from blood.…”
Section: Methodsmentioning
confidence: 99%
“…DNAemia was quantified weekly or bi-weekly upon occurrence of active HCMV infection. Pre-emptive antiviral therapy was given to Tx patients reaching a DNAemia cut-off of 300 000 DNA copies ml À1 whole blood (Lilleri et al, 2004;Gerna et al, 2007Gerna et al, , 2011 and consisted of iv ganciclovir (GCV) at a dosage of 5 mg kg À1 twice a day, or oral valganciclovir (VGCV), 900 mg twice a day. Antiviral therapy was continued until the virus disappeared from blood.…”
Section: Methodsmentioning
confidence: 99%
“…Under proinflammatory conditions, the placenta may express atypical receptors and molecules, facilitating CMV transplacental passage (31)(32)(33)(34). The third hypothesis is that the strong T-cell response observed for cCMV may be directly related to a preceding protracted or high-level viremia: evidence from the transplant field suggests that high viral loads in blood promote higher-level T-cell responses (35). The latter hypothesis would be technically difficult to assess for pregnancy since T-cell assays are performed after the occurrence of CMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, other transplantation studies have also indicated an important role for CD4 1 T cells in CMV viral control after transplantation (24)(25)(26)(27)(28). Interestingly, in a study of renal, heart, and lung transplantation recipients, lung transplantation recipients had Figure 4.…”
Section: Discussionmentioning
confidence: 99%